Reaktualisasi Etika Lingkungan Islam dan Tafsir Bimā Kasabat Aydī Al-Nās QS Al-Rum 41 Dalam Krisis Global - Fadli, Nazar; Faisal, Muhammad; Hidayah, Maula (Prodi Ilmu Al-Qur'an dan Tafsir, 2025)
The global environmental crisis reveals that ecological degradation is not merely the result of technical failures in environmental management, but also of an exploitative worldview governing human–nature relations. Within Muslim societies, Islam is often portrayed as environmentally friendly; however, Islamic environmental ethics remain largely confined to individual moral teachings and normative–theological discourse. This article examines the limitations of normative moral-religious approaches in responding to the global environmental crisis and proposes a reactualization of Islamic environmental ethics as a transformation of the human–nature relational paradigm. The novelty of this article lies in positioning Islamic environmental ethics not merely as a normative moral doctrine, but as a critical ethical framework intended to shape public decision-making and development structures. Using a qualitative approach through critical literature review of Qur’anic exegesis, Islamic ethics, and contemporary environmental studies, this study finds that while Islamic environmental ethics possess strong normative foundations, they have not yet functioned as an ecological framework shaping public policy. This article argues that the reactualization of Islamic environmental ethics must be directed toward a critical ethical paradigm capable of transforming human–nature relations in a just and sustainable manner.